2014
DOI: 10.1007/s10826-014-0047-9
|View full text |Cite
|
Sign up to set email alerts
|

The Value of a Smile: Child Positive Affect Moderates Relations Between Maternal Emotion Dysregulation and Child Adjustment Problems

Abstract: Little is known about how processes underlying maternal psychopathology, such as emotion dysregulation, are related to children's adjustment problems. Further, scant research has explored child protective factors that can buffer these associations. We used a multi-method approach to examine whether child positive affect functions as a protective and/or promotive factor in the context of maternal emotion dysregulation in a cross-sectional sample of 95 mothers (M age = 30.38 years, SD = 6.10) and their preschool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…As mother's race, marital status, and education significantly differed among clusters, a composite risk variable was created to serve as a covariate, by dichotomizing and summing each variable (see Davis et al., ). Post hoc ANCOVAs were conducted to examine cluster differences in parenting after accounting for these contextual variables.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As mother's race, marital status, and education significantly differed among clusters, a composite risk variable was created to serve as a covariate, by dichotomizing and summing each variable (see Davis et al., ). Post hoc ANCOVAs were conducted to examine cluster differences in parenting after accounting for these contextual variables.…”
Section: Resultsmentioning
confidence: 99%
“…Emotional responses comprise subjective feelings, observable behaviors, and physiological responses, and regulation includes both conscious/voluntary and unconscious processes (Gross, ). Currently, there are many ways to measure ER (e.g., self‐ and informant reports, psychophysiological assessments, behavioral observations) and concordance across different levels of analysis is inconsistent (Calkins & Dedmon, ; Davis, Suveg, & Shaffer, ). These divergent findings make it difficult to decipher how individual components of the broader ER construct fit together to inform us about key psychosocial processes for parents and children.…”
mentioning
confidence: 99%
“…Somewhat similarly, Davis et al. (2015) reported that mothers’ RSA suppression from baseline to a speech task in which they described their parenting philosophy was not significantly associated with their reports on the DERS ( r = −.08); and only the DERS predicted mothers reports of their preschoolers’ behavior problems.…”
mentioning
confidence: 89%
“…Likewise, although results of basic research studies have demonstrated associations between elevated DERS scores and less adaptive parenting and child outcomes (Carreras, Carter, Heberle, Forbes, & Gray, 2019; Sarıtaş, Grusec, & Gençöz, 2013; Shaffer & Obradovic, 2017), this research has focused on parents of preschool aged or older children and has often utilized self‐reported indices of parenting (e.g., Jones, Brett, Ehrlich, Lejuez, & Cassidy, 2014; Morelen, Shaffer, & Suveg, 2016) and mother‐reported child outcomes (e.g., Davis, Suveg, & Shaffer, 2015; Morelen et al., 2016) which suffer also from shared source variance. Thus, there is a need to determine if mothers’ reports on the DERS correlate with observed indices of parenting and child outcomes during infancy.…”
mentioning
confidence: 99%
“…Meta-analyses demonstrate a large effect of (low) positive affectivity on internalizing disorders (Kotov, Gamez, Schmidt, & Watson, 2010), especially depression (Klein, Dyson, Kujawa, & Kotov, 2012). Interest in the role of positive affectivity in developmental psychopathology has been on the rise, and both main effects and interactions with environmental factors have been proposed (Davis & Suveg, 2014; Davis, Suveg, & Shaffer, 2015; Wills, Sandy, Yaeger, & Shinar, 2001). Thus, children whose positive affectivity is dampened might be differentially susceptible to their environments.…”
Section: Biobehavioral Plasticity Factors Explaining Internalizing Prmentioning
confidence: 99%